Bery Engebretsen letter to James J. Dinsmore regarding summer bird sightings, summer 1997 - Engebretsen, Beryet al (1997)
Letter from Bery Engebretsen to James J. Dinsmore regarding summer bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1997. Epson - sheet feed/flatbed